Host heterogeneity affects both parasite transmission to and fitness on subsequent hosts. (13th March 2017) - Stephenson, Jessica F.; Young, Kyle A.; Fox, Jordan; Jokela, Jukka; Cable, Joanne; Perkins, Sarah E.
Abstract : Infectious disease dynamics depend on the speed, number and fitness of parasites transmitting from infected hosts ('donors') to parasite-naive 'recipients'. Donor heterogeneity likely affects these three parameters, and may arise from variation between donors in traits including: (i) infection load, (ii) resistance, (iii) stage of infection, and (iv) previous experience of transmission. We used the Trinidadian guppy, Poecilia reticulata, and a directly transmitted monogenean ectoparasite, Gyrodactylus turnbulli, to experimentally explore how these sources of donor heterogeneity affect the three transmission parameters. We exposed parasite-naive recipients to donors (infected with a single parasite strain) differing in their infection traits, and found that donor infection traits had diverse and sometimes interactive effects on transmission. First, although transmission speed increased with donor infection load, the relationship was nonlinear. Second, while the number of parasites transmitted generally increased with donor infection load, more resistant donors transmitted more parasites, as did those with previous transmission experience. Finally, parasites transmitting from experienced donors exhibited lower population growth rates on recipients than those from inexperienced donors. Stage of infection had little effect on transmission parameters. These results suggest that a more holistic consideration of within-host processes will improve our understanding of between-host transmission and hence disease dynamics. This article is part of the themed issue 'Opening the black box: re-examining the ecology and evolution of parasite transmission'.